The Integrative Model in Qur'anic Interpretation at UIN Sunan Kalijaga: A Contributory Analysis of the Ma'na-cum-Maghza and Maqasidi Approaches - Mahbub Ghozali; Imam Bustomi (Contemporary Quran, 2025)
This study examines the integrative model of Qur'anic interpretation developed at UIN Sunan Kalijaga, with a focus on the contributions of two contemporary approaches: ma'na-cum-maghza and maqasidi. These approaches represent scholarly efforts to merge textual meaning with contextual relevance in understanding the message of the Qur'an. The ma'na-cum-maghza approach emphasizes uncovering the deeper meanings behind the text, while the maqasidi approach centers on the universal objectives and values that sharia aims to realize. Through a literature review and analysis of academic works produced at UIN Sunan Kalijaga, this study demonstrates that the integrative model not only enriches tafsir methodology but also offers a more adaptive response to the challenges of the modern era. As such, this model makes a significant contribution to the development of a contextual, relevant, and transformative Qur'anic interpretation.